2022
DOI: 10.3389/fphys.2022.870399
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic and Antihyperlipidemic Effects of Methanolic Extract of Leaves of Spondias mombin in Streptozotocin-Induced Diabetic Rats

Abstract: Objective:Spondias mombin is a plant that reported to have anticonvulsant, antimicrobial, antioxidant, antiulcer, antiasthmatic, and wound healing activities. Diabetes dyslipidemic effect of Spondias mombin leaves is not clear. Hence, current study planned to evaluate the antidiabetic and antihyperlipidemic effects of methanolic extract of leaves of Spondias mombin (MESM) in streptozotocin (STZ) induced diabetic rats.Methods: Phytochemicals were determined by standard method and antioxidant activity was determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The anticancer potential of carotenoid isolates from the leaves of S. mombin has been documented by Metibemu et al. 26 Although previous studies have reported the antidiabetic activity of S. mombin leaves, 10 , 11 the antidiabetic efficacy of solvent fractions of S. mombin stem bark in the HSD-induced diabetes Drosophila model has not been explored.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The anticancer potential of carotenoid isolates from the leaves of S. mombin has been documented by Metibemu et al. 26 Although previous studies have reported the antidiabetic activity of S. mombin leaves, 10 , 11 the antidiabetic efficacy of solvent fractions of S. mombin stem bark in the HSD-induced diabetes Drosophila model has not been explored.…”
Section: Resultsmentioning
confidence: 99%
“…9 The antidiabetic potential of S. mombin leaves has been reported in alloxan-induced rats 10 and streptozotocin-induced diabetic rats. 11 The hypoglycemic effect of S. mombin stem bark has been reported in healthy rats. 12 After establishing high-sucrose diet (HSD)-induced diabetes in Drosophila as in previous studies, 5 , 13 this study investigated the antidiabetic potential of ethyl acetate and n-butanol fractions of S. mombin stem bark in this HSD-induced Drosophila model.…”
Section: Introductionmentioning
confidence: 99%
“…This could be due to the sufficient intake of glucose by the cells after the treatment with glibenclamide or S. torvum fruit extract. Most of the experimental studies suggested that increased gluconeogenesis is a main source of hyperglycemia in insulin deficiency ( 65 ). It is also suggested that insulin may inhibit PCK1 gene transcription by activation of a possible insulin response factors ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because glucose is used up more slowly in diabetics, a condition called diabetesinduced hyperlipidemia is to blame for the excessive release of fat from adipose tissue. 23 Treatment with a polyherbal formulation resulted in lower levels of cholesterol, triglyceride, and LDL, and higher levels of HDL, which is suggestive of the formulations' potential ability to lower blood lipid levels (hypolipidemic activity).…”
Section: Body Weight Of Ratsmentioning
confidence: 98%
“…The long-term health effects of hyperglycemia include damage and eventual failure of several organs, most notably the nerves, blood vessels, kidneys, eyes, and heart. 1,2 Diabetes is currently becoming a serious concern on a global scale and a main cause of morbidity and death in the majority of countries. It is estimated that there are 382 million individuals who are affected by the disease, and 5.1 million people lost their lives to diabetes in 2013.…”
Section: Introductionmentioning
confidence: 99%